Temporal and spatial evolution of maternal and neonatal mortality rates in Brazil, 1997–2012 - Nádia Cristina Pinheiro Rodrigues; Denise Leite Maia Monteiro; Andréa Sobral de Almeida; Mônica Barros de Lima Barros; André Pereira Neto; Gisele O’Dwyer; Mônica Kramer de Noronha Andrade; Matthew Brian Flynn; Valéria Teresa Saraiva Lino (Jornal de Pediatria, 2016)
Objective: Maternal and neonatal mortality are important public health issues in low-income countries. This study evaluated spatial and temporal maternal and neonatal mortality trends in Brazil between 1997 and 2012. Methods: This study employed spatial analysis techniques using death records from the mortality information system. Maternal mortality rates per 100,000 and neonatal mortality rates (early and late) per 1000 live births were calculated by state, region, and period (1997–2000, 2001–2004, 2005–2008, and 2009–2012). Multivariate negative binomial models were used to explain the risk of death. Results: The mean Brazilian maternal mortality rate was 55.63/100,000 for the entire 1997–2012 period. The rate fell 10% from 1997–2000 (58.92/100,000) to 2001–2004 (52.77/100,000), but later increased 11% during 2009–2012 (58.69/100,000). Early and late neonatal mortality rates fell 33% (to 7.36/1000) and 21% (to 2.29/1000), respectively, during the 1997–2012 period. Every Brazilian region witnessed a drop in neonatal mortality rates. However, maternal mortality increased in the Northeast, North, and Southeast regions. Conclusion: Brazil's neonatal mortality rate has improved in recent times, but maternal mortality rates have stagnated, failing to meet the Millennium Development Goals. Public policies and intersectoral efforts may contribute to improvements in these health indicators. Resumo: Objetivo: A mortalidade materna e neonatal é um importante problema de saúde pública em países de baixa renda. Este estudo avaliou as tendências de mortalidade materna e neonatal espacial e temporal no Brasil entre 1997 e 2012. Métodos: Este estudo utilizou técnicas de análise espacial utilizando registros de óbito do Sistema de Informações sobre Mortalidade. As taxas de mortalidade materna a cada 100.000 e as taxas de mortalidade neonatal (precoce e tardia) a cada 1.000 nascidos vivos foram calculadas por estado, região e período (1997-2000, 2001-2004, 2005-2008 e 2009-2012). Os modelos binomiais negativos multivariados foram utilizados para explicar o risco de morte. Resultados: A taxa de mortalidade materna no Brasil foi 55,63/100.000 em todo o período entre 1997 e 2012. A taxa caiu 10% de 1997-2000 (58,92/100.000) a 2001-2004 (52,77/100.000), porém, mais tarde, aumentou 11% até 2009-2012 (58,69/100.000). As taxas de mortalidade neonatal precoce e tardia caíram 33% (para 7,36/1.000) e 21% (para 2.29/1.000), respectivamente, durante o período de 1997-2012. Toda região brasileira testemunhou uma queda nas taxas de mortalidade neonatal. Contudo, a mortalidade materna aumentou nas regiões Nordeste, Norte e Sudeste. Conclusão: A taxa de mortalidade neonatal do Brasil melhorou nos últimos anos, porém as taxas de mortalidade materna estagnaram, deixando de atingir os Objetivos de Desenvolvimento do Milênio. As políticas públicas e os esforços intersetoriais poderão contribuir para as melhorias nesses indicadores de saúde. Keywords: Maternal mortality, Infant mortality, Trends, Maternal health, Ecological studies, Mortality, Palavras-chave: Mortalidade materna, Mortalidade infantil, Tendências, Saúde maternal, Estudos ecológicos, Mortalidade